Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Karyawan CV. Pilar Emas Jember - Ajeng Windy Puspitasari; Sutrisno Sutrisno; I Ketut Mastika (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2023)
The purpose of this study was to examine the influence of workload and job stress on employee performance at CV. Pilar Emas Jember. This research was conducted using a quantitative research method and collected data through a questionnaire. The research sample consisted of 53 employees, which were part of the total population of 62 employees at CV. Pilar Emas. The sampling technique used in this research was proportionate stratified random sampling. Instrument testing was conducted using validity and reliability tests. This study employed multiple linear regression analysis to test the hypotheses regarding the influence of workload and job stress on employee performance, and the results indicated that workload and job stress have a significant influence on employee performance at CV. Pilar Emas.